A New Rabies Vaccine Based on a Recombinant Orf Virus (Parapoxvirus) Expressing the Rabies Virus Glycoprotein - Amann, Ralf (American Society for Microbiology, 2013)
The present study describes the generation of a new Orf virus (ORFV) recombinant, D1701-V-RabG, expressing the rabies virus (RABV) glycoprotein that is correctly presented on the surface of infected cells without the need of replication or production of infectious recombinant virus. One single immunization with recombinant ORFV can stimulate high RABV-specific virus-neutralizing antibody (VNA) titers in mice, cats, and dogs, representing all nonpermissive hosts for the ORFV vector. The protective immune response against severe lethal challenge infection was analyzed in detail in mice using different dosages, numbers, and routes for immunization with the ORFV recombinant. Long-term levels of VNA could be elicited that remained greater than 0.5 IU per ml serum, indicative for the protective status. Single applications of higher doses (10(7) PFU) can be sufficient to confer complete protection against intracranial (i.c.) challenge, whereas booster immunization was needed for protection by the application of lower dosages. Anamnestic immune responses were achieved by each of the seven tested routes of inoculation, including oral application. Finally, in vivo antibody-mediated depletion of CD4-positive and/or CD8-posititve T cell subpopulations during immunization and/or challenge infection attested the importance of CD4 T cells for the induction of protective immunity by D1701-V-RabG. This report demonstrates another example of the potential of the ORFV vector and also indicates the capability of the new recombinant for vaccination of animals.